Faktor-Faktor Yang Mempengaruhi Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Meral Karimun Tahun 2023 - Lady Harnofive; Siska Natalia; Rizki Sari Utami (STIKes Ibnu Sina Ajibarang, 2023)
Pneumonia is a deadly disease in the world. Pneumonia in toddlers in Indonesia is still a major health problem. This can be seen from the high mortality rate in toddlers or pneumonia mortality in toddlers. One effort to reduce pneumonia cases is by knowing the risk factors that cause pneumonia. This study aims to determine the risk factors associated with the incidence of pneumonia in children under five in the Meral Community Health Center Working Area in 2023. This study used a quantitative cross sectional design. The number of samples in this research was 100 respondents, and was obtained using the accidental sampling method. Data was collected by filling out questionnaires and supported by medical record data or the respondent's MTBS form to see the diagnosis, and the KIA book to confirm the history of the toddler's characteristics. The results of this study showed that 57 respondents (57%) experienced pneumonia. The conclusion of this study is that there is a relationship between residential density and the smoking status of family members on pneumonia, but there is no relationship between the nutritional status of toddlers and pneumonia. Suggestions for Meral Community Health Center nurses to provide education to parents of toddlers regarding efforts to prevent pneumonia, especially in terms of reducing smoking habits in the house and adjusting the number of residents to the size of the house where they live.